2021
DOI: 10.1016/j.jocd.2021.07.007
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Vertebral Bone Density on Chest CT in Hospitalized COVID-19 Patients

Abstract: Purpose : To evaluate the prognostic value of the vertebral bone mineral density (BMD) on chest computed tomography (CT) in COVID-19 patients. Methods : The chest CT of hospitalized patients with COVID-19 pneumonia were evaluated for Pneumonia Severity Score (PSS) as the ratio of the volume of involved lung parenchyma to the total lung volume. In addition, BMD was manually measured from the vertebral corpus using axial CT images. The relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 30 publications
0
25
0
1
Order By: Relevance
“… 21 In addition, recent studies also demonstrated that low BMD could be the predictor of the severe outcomes and mortality of the respiratory infections among patients with Coronavirus disease 2019 (COVID-19). The low vertebral BMD was significantly associated with the higher mortality of patients with COVID-19, 22 and low BMD at thoracic vertebra can predict whether intensive care treatment is needed for patients with COVID-19. 23 Our study further showed that low BMD is not only a potential prognostic factor in patients with infections or sepsis, but also a novel risk factor of infections and sepsis.…”
Section: Discussionmentioning
confidence: 95%
“… 21 In addition, recent studies also demonstrated that low BMD could be the predictor of the severe outcomes and mortality of the respiratory infections among patients with Coronavirus disease 2019 (COVID-19). The low vertebral BMD was significantly associated with the higher mortality of patients with COVID-19, 22 and low BMD at thoracic vertebra can predict whether intensive care treatment is needed for patients with COVID-19. 23 Our study further showed that low BMD is not only a potential prognostic factor in patients with infections or sepsis, but also a novel risk factor of infections and sepsis.…”
Section: Discussionmentioning
confidence: 95%
“…Different from the previous study, Tahtabasi et al measured BMD at L1 level, using a cut-off value of 100 HU to define low density. In the lower BMD group, they observed a significantly higher rate of ICU admission (33.4% vs. 21.2%) as a result of univariate analysis [ 43 ].…”
Section: Chest Ct As a Prognostic Tool In Covid-19 Patientsmentioning
confidence: 99%
“…analyses [26]. Although it is conceivable that severe VFx may affect respiratory mechanics [27], it is more likely that prevalent fractures are a feature of frailty and additional comorbidities that suggest a worse prognosis in COVID-19.…”
Section: Accepted Manuscriptmentioning
confidence: 99%